PENGARUH TUMPUKAN DAN LAMA MASA SIMPAN PAKAN PELET TERHADAP KUALITAS FISIK - Achmad Jaelani; Siti Dharmawati; Wacahyono wacahyono (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2016)
Feed industry produce of  large scale process and large quantities of ration. If feed are numerous, and are not exhausted once the distribution, then the stability of such goods must be maintained to keep the quality. This is of course requires a system  effective warehousing and storage for the finished products manufactured. Therefore, this study aimed to determine the effect stacks and time storage of the physical quality commercial feed. The study used a completely randomized design with a time storage treatment for 3, 6, 9, and 12 days. Each treatment using 5 replicates. Data for quality testing the physical form of the density of the stack, heap compaction density, smoothness, and impact resistance was analyzed using ANOVA and if  treatment gave significantly different effect will be tested by Duncan's multiple range test. The results showed that the height of the stack and a time storage effect on the density of the stack, heap compaction density, smoothness, and impact resistance, and there is interaction between pile heights and long shelf life of the heap compaction density and impact resistance. Good feed must be kept within a period of not more than 13 days and storage methods must be considered as good as the number of stacks, room humidity and cleanliness, because the longer the food is stored with the condition stacked excess will make the feed more easily destroyed, which in turn will further exacerbate the physical condition of the feed when distributed to the consumers.